1996
DOI: 10.1159/000262361
|View full text |Cite
|
Sign up to set email alerts
|

Fluoridation of Hydroxyapatite Powder by Ammonium Hexafluorosilicate

Abstract: Diamine silver fluoride [AgF: (NH3)2AgF] is a unique fluoride solution used clinically in Japan for primary teeth. AgF has been shown to reduce dental caries and dentine hypersensitivity. However, AgF also stains teeth black due to sulfide precipitation and thus is unacceptable for permanent teeth. In the present study, the potential value of ammonium hexafluorosilicate [SiF: (NH4)2SiF6], which has a formula similar to that of AgF but contains no Ag, was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…For this esthetic reason, the use of ammonium hexafluorosilicate (AHF) solution, which replaces the silver component with silica, has been suggested for prevention of caries progression (19). Several studies have indicated that AHF treatment does not produce tooth staining; upon application, a large amount of precipitate forms on the tooth surface, and the acidity of the solution causes etching of the hard tissues of the tooth and re-precipitation of calcium and phosphate ions as silica-calcium-phosphate crystals (18)(19)(20)(21). It has been emphasized that the antibacterial activity of AHF solution may be increased when it is used along with several antibacterial agents, such as cetylpyridinium chloride.…”
Section: Introductionmentioning
confidence: 99%
“…For this esthetic reason, the use of ammonium hexafluorosilicate (AHF) solution, which replaces the silver component with silica, has been suggested for prevention of caries progression (19). Several studies have indicated that AHF treatment does not produce tooth staining; upon application, a large amount of precipitate forms on the tooth surface, and the acidity of the solution causes etching of the hard tissues of the tooth and re-precipitation of calcium and phosphate ions as silica-calcium-phosphate crystals (18)(19)(20)(21). It has been emphasized that the antibacterial activity of AHF solution may be increased when it is used along with several antibacterial agents, such as cetylpyridinium chloride.…”
Section: Introductionmentioning
confidence: 99%
“…For prevention of dental caries and treatment of dentin hypersensitivity, ammonium hexafluorosilicate (AHF; (NH 4 ) 2 SiF 6 ) was applied to permanent teeth to overcome tooth discoloration caused by SDF treatment (10). AHF increases the acid resistance of enamel and dentin to almost the same extent as SDF (11).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the use of natural raw materials for the synthesis of HAp enables it to be accepted better by the organism because of its similar physical-chemical characteristics 27,28,35 . Calcium carbonate for the synthesis of calcium phosphates similar to bone can be obtained from several natural sources.…”
Section: Introductionmentioning
confidence: 99%